HEDONIC VALUATION OF MARGINAL WILLINGNESS TO PAY FOR AIR QUALITY IMPROVEMENT - Endah Saptutyningsih; Agus Tri Basuki (Economic Journal of Emerging Markets, 2014)
Abstract This study aims to identify the highest air pollution areas and to estimate household marginal willingness to pay for air quality improvement. The result of Kriging technique indicates that six sub districts in Yogyakarta City and one sub district in Gunungkidul have highest concentration of particle pollution (PM10). The result of hedonic price method conclude that by adopting a two-stage estimation procedure an 1% increase in the level of PM10 reduced property prices in the study area by 0.32%. Marginal implicit price for reducing PM10 is Rp 957,900.00. The households are willing to pay an additional amount of 1.34 percent for a reduction in PM10 by 1%. Keywords: Air pollution, marginal willingness to pay, hedonic price, implicit priceJEL classification numbers: D12, Q53